2019
DOI: 10.1002/ijc.32011
|View full text |Cite
|
Sign up to set email alerts
|

Strong associations of a healthy lifestyle with all stages of colorectal carcinogenesis: Results from a large cohort of participants of screening colonoscopy

Abstract: The risk of developing colorectal cancer (CRC) is associated with a wide range of dietary and lifestyle factors. The individual contribution of single modifiable factors, such as alcohol consumption, physical activity, smoking, body mass index (BMI) or dietary components, to the development of CRC has been investigated extensively, but evidence on their combined effect at various stages of colorectal carcinogenesis is sparse. The aim of our study was to analyze the association of a healthy lifestyle pattern wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…In the past decade, the incidence of CRC in China has increased in the aged population. The highest incidence of CRC is in individuals >50 years old (8). The present study demonstrated that the percentage of patients with schistosomal and nonschistosomal CRC in patients >50 years old was 56.88%.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In the past decade, the incidence of CRC in China has increased in the aged population. The highest incidence of CRC is in individuals >50 years old (8). The present study demonstrated that the percentage of patients with schistosomal and nonschistosomal CRC in patients >50 years old was 56.88%.…”
Section: Discussionsupporting
confidence: 47%
“…In China, colorectal cancer (CRC) is one of the top five leading causes of cancer-associated death in men and women (7). A number of risk factors for CRC in Asia have been identified, including age, sex, family history and a high body fat percentage (8). The association between schistosomiasis and CRC has been determined previously (9) and large epidemiological studies have demonstrated an association between CRC and schistosomiasis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A healthy lifestyle score was created based on the established evidence on CRC risk and protective factors, notably smoking, alcohol consumption, physical activity and body mass index (BMI) [63] (Table S4). It was adapted from a score created by Carr et al that was associated with lower risk for all stages of CRC [73,74]. Specifically, respondents were attributed one point for the following low-CRC-risk behaviours: non-smoking or occasional smoking, consumption of less than two alcoholic drinks per day, being physically active (at least 150 min per week spent on doing sports, fitness or recreational physical activities, in line with World Health Organization Global Recommendations on Physical Activity for health [75]) and having a BMI below 25 kg/m 2 , i.e., not being overweight or obese [63].…”
Section: Derivation Of the Healthy Lifestyle Scorementioning
confidence: 99%
“…In addition, CRC still represents the third leading cause of cancer-related deaths for both men and women in Italy [6, 7].Adherence to a healthy lifestyle is associated with a reduced risk of colorectal cancer regardless of individuals' genetic risk [8]. It has been found that a healthy lifestyle is strongly associated with lower risk of all stages of colorectal neoplasms [9]. Erben et al [9] highlighted the importance of a healthy lifestyle early in the beginning of the carcinogenic process and strengthened its relevance for primary prevention purposes.…”
mentioning
confidence: 99%
“…It has been found that a healthy lifestyle is strongly associated with lower risk of all stages of colorectal neoplasms [9]. Erben et al [9] highlighted the importance of a healthy lifestyle early in the beginning of the carcinogenic process and strengthened its relevance for primary prevention purposes. However, Ladabaum, et al [4] reported di culties in implementing major lifestyle changes or widespread primary prevention strategies to decrease CRC risk.…”
mentioning
confidence: 99%